Effects Of Music Therapy On Clinical And Biochemical Parameters Of Metabolic Syndrome - Sharma, Madhuri; Rajnee, Dr; Mathur, Kamlesh Chandra (Journal of Bangladesh Society of Physiologist, 2012)
Background: Music therapy is a new approach being used for the management of metabolic abnormalities and stress related illness. Objective: To study the effect of Music therapy on various clinical and biochemical parameters of Metabolic Syndrome. Methods: This cross sectional study was carried out on 100 patients of metabolic syndrome selected randomly. These patients were divided into two equal groups after age, sex adjustment. In control group (group I) 50 patients underwent the conventional treatment. 50 patients in study group were treated with supervised music protocol along with conventional treatment. The Body Mass Index, ;Waist-Hip ratio, Blood pressure, Fasting blood sugar were monitored weekly while HbA1c and lipid profile were determined at the baseline and after three months of exposure to music therapy. Statistical analysis was performed by employing student t- test. Results: In the study group there was a significant decrease in BMI (27.18±5.02 to 25.44±3.49 kg/m2, p<0.05), waist hip ratio (0.95±0.05 to 0.93±0.05 cm, p<0.05), Fasting blood sugar (196.00±47.80mg/ dl to152.00±16.19mg/dl , p<0.001), HbA1c (8.41±1.31% to 7.08±0.78 % p<0.001), Systolic Blood Pressure (151.00±12.10 to 136±9.04 mmHg p<0.001), Diastolic Blood Pressure (94±4.80 to 86.44±3.16 mmHg, p<0.01), Mean serum cholesterol (257.80±18.92 to 229.12±17.82mg/dl, p<0.001) and triglycerides (180.86±14.04 to 136.50±8.92mg/dl, p<0.001), LDL (167.97±14.40 to 140.20±15.41mg/dl, p<0.001), and VLDL (33.60±2.88 to 28.04±3.08mg/dl, p<0.001) and increase in HDL (33.32±3.38 to 39.71±3.41mg/dl, p<0.001), when compared with those of control group not receiving the music therapy along with the conventional treatment. Conclusion: The promising outcomes of Music therapy showed that it may be considered as a useful adjunct to conventional treatment in management of the metabolic syndrome. This study advocates music therapy to establish it from a general well being concepts to a neuroscience guided model. DOI: http://dx.doi.org/10.3329/jbsp.v6i2.9760 JBSP 2011 6(2): 108-115